2019
DOI: 10.1073/pnas.1813206116
|View full text |Cite
|
Sign up to set email alerts
|

Earth history and the passerine superradiation

Abstract: Avian diversification has been influenced by global climate change, plate tectonic movements, and mass extinction events. However, the impact of these factors on the diversification of the hyperdiverse perching birds (passerines) is unclear because family level relationships are unresolved and the timing of splitting events among lineages is uncertain. We analyzed DNA data from 4,060 nuclear loci and 137 passerine families using concatenation and coalescent approaches to infer a comprehensive phylogenetic hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
304
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 295 publications
(343 citation statements)
references
References 99 publications
(186 reference statements)
25
304
2
Order By: Relevance
“…The ability to incorporate museum specimens into modern molecular systematics offers plenty of research possibilities, as evidenced by the plethora of studies published in recent years. One obvious benefit in systematics is the inclusion of rare, difficult to collect, endangered or extinct taxa in phylogenomic analyses (Hedin et al, ; Hedin, Derkarabetian, Blair, et al, ; Hedin, Derkarabetian, Ramírez, et al, ; Oliveros et al, ; Tsai et al, ; Wood et al, ), or even datasets consisting entirely of museum specimens (Tsai et al, ). One important consideration will be the proportion of specimens in the final dataset that are historical museum specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to incorporate museum specimens into modern molecular systematics offers plenty of research possibilities, as evidenced by the plethora of studies published in recent years. One obvious benefit in systematics is the inclusion of rare, difficult to collect, endangered or extinct taxa in phylogenomic analyses (Hedin et al, ; Hedin, Derkarabetian, Blair, et al, ; Hedin, Derkarabetian, Ramírez, et al, ; Oliveros et al, ; Tsai et al, ; Wood et al, ), or even datasets consisting entirely of museum specimens (Tsai et al, ). One important consideration will be the proportion of specimens in the final dataset that are historical museum specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, museum specimens can be considered genomic resources (McCormack, Rodríguez-Gómez, Tsai, & Faircloth, 2017) and can be used for diverse types of studies. Examples of such studies are fine-scale population genomics and genotyping (Bi et al, 2013;Lim & Braun, 2016), genome sequencing (Staats et al, 2013), metagenomics (Der Sarkissian et al, 2017), epigenomics (Rubi, Knowles, & Dantzer, 2019), barcoding (Miller, Beentjes, van Helsdingen, & IJland, 2013); Prosser, deWaard, Miller, & Hebert, 2016), species delimitation (Hedin, Derkarabetian, Blair, & Paquin, 2018;Kehlmaier et al, 2019), and phylogenomics (Blaimer, Lloyd, Guillory, & Brady, 2016;Hedin, Derkarabetian, Ramírez, Vink, & Bond, 2018;Ruane & Austin, 2017;Sproul & Maddison, 2017;Starrett et al, 2017;Wood, González, Lloyd, Coddington, & Scharff, 2018), including phylogenomic studies that incorporate genetic data from rare, endangered and/or extinct taxa held in historical collections (Hedin, Derkarabetian, Blair, et al, 2018;Oliveros et al, 2019;Tsai et al, 2019). This was not the case just a few years ago, when historical museum samples were not routinely used for molecular work.…”
mentioning
confidence: 99%
“…We obtained six empirical datasets that employed different calibration strategies from five published studies (Table 1) (Bond et al 2014;Tong et al 2015;Barba-Montoya et al 2017;Nauheimer et al 2018;Oliveros et al 2019). Molecular data were obtained from supplementary files of original studies.…”
Section: Empirical Analysesmentioning
confidence: 99%
“…RelTime analyses were conducted in MEGA X . For Oliveros et al (2019)'s data, the published Bayesian timetree was summarized from 10 timetrees inferred using 10 different random subsets of the full dataset, because BEAST was computationally infeasible to analyze the full dataset. Since the original study has shown that 10 subsets provided similar results, we only conducted RelTime analysis using one subset.…”
Section: Empirical Analysesmentioning
confidence: 99%
“…Among the oscine passerines, by far the largest radiation of birds, these resources are limited to five species from the Passerides clade. Yet the early evolution of the Oscines involved multiple branching in the Australo‐Papuan region in the Oligocene before the emergence of the Corvides and Passerides, the two groups that ultimately gave the oscines their numerical and ecological dominance (Marki et al, ; Oliveros et al, ). The superb fairy‐wren is an exemplar of the largest clade of that early radiation, the Meliphagides, which has almost 300 species.…”
Section: Introductionmentioning
confidence: 99%